On tatay's boat - Enriquez, Ma. Cecilia A.; Yumul, Nelz. ([S.l. s.n.], 2010)
"Tatay teaches his son great life lessons about respect for nature, the value of friendship, and the difference little acts of goodness can make -- through his stories about his underwater friends."